Effect of Intrahepatic Cholestasis of Pregnancy (ICP) on Neonatal Outcome - Begum, Nargis Ara; Chaudhury, Israt Jahan; Bari, Nahla; Afroze, Sharmin (Dhaka Shishu (Children) Hospital Journal, 2022)
Intrahepatic cholestasis of pregnancy is a condition unique to pregnancy characterized by pruritus and elevated serum bile acids and/or aminotransferase levels. It usually manifests during second or third trimester of pregnancy and improves after delivery. But neonates are at increased risks of still birth, prematurity, respiratory distress syndrome and metabolic problems. Timely identification and appropriate intervention can reduce the adverse neonatal outcomes. DS (Child) H J 2021; 37(2): 135-139